Regulating advanced biomedical technologies: A modern criminal law perspective - Hakobyan, Anush; Sargsyan, Adelina; Bayanduryan, Hovhannes; Manukyan, Nonna (Edelweiss Applied Science and Technology, 2024)
This study explores the urgent need for criminal law to address the advancements in biomedical technologies, particularly focusing on cloning. It highlights the dichotomy between the potential therapeutic benefits of cloning technologies, such as combating hereditary diseases, and their possible misuse. The paper discusses international legal frameworks and declarations, such as the United Nations Declaration on Human Cloning and the Council of Europe Convention on Human Rights and Biomedicine, which seek to navigate the ethical and legal challenges of cloning. The distinction between therapeutic and reproductive cloning is emphasized, with therapeutic cloning offering significant medical advancements raising profound ethical concerns, particularly regarding the moral status of the embryo. The paper critiques the current legislative landscape in the Republic of Armenia, which it finds insufficient in addressing the complexities introduced by these technologies, suggesting a need for comprehensive legal reform to safeguard human dignity and genetic integrity within the context of modern medicine.